DAMPAK POSITIF PARIWISATA TERHADAP BUDAYA, EKONOMI, DAN LINGKUNGAN DI KASEPUHAN CIPTA MULYA (KRITIS, 2022)
Tourism has become the most sustainable and promising sector in Indonesia because all aspects of society experience the positive impacts of tourism. In addition to the community, the tourism sector also positively impacts cultural, economic, and environmental aspects. Kasepuhan Cipta Mulya is one of the traditional Sundanese villages that, since 2012, has received tourist visits. After becoming a tourist destination and being visited by many tourists, the people of Kasepuhan began to experience the positive impact of tourism. This study aims to determine the positive impact on cultural, economic, and environmental aspects in Kasepuhan Cipta Mulya after many tourist visits. This study uses qualitative methods with data collection techniques, including field observations and interviews. Through this research, it can be concluded that tourism positively impacts cultural, economic, and environmental aspects in Kasepuhan Cipta Mulya. The entire Kasepuhan community can experience this positive impact. The community is also very open and welcomes tourists to Kasepuhan Cipta Mulya.